Turkey Workforce Development : SABER Country Report 2012 - World Bank Group (World Bank, Washington, DC, 2015)
Although Turkey experienced prosperous growth during the early and mid-2000s, similar success could not be achieved in increasing the employment rate. The Turkish economy, which had already started to slow down in 2007, was severely affected by the global economic crisis in 2008, and the global financial turmoil led to a sharp contraction starting in the last quarter of 2008. The Recovery began in the last quarter of 2009 and was rapid, with growth reaching 9 percent in 2010 and 8.5 percent in 2011. Successful development of the workforce requires a Technical and vocational education and training (TVET) system that is aligned with the needs of the labor market. The ‘Strengthening Vocational and Technical Education and Training Project’ (SVET), launched in 2005, aimed to address the mismatch between education and training programs and the needs of the labor market. Among other achievements, the SVET program resulted in the establishment of the Vocational Qualifications Authority and the development of modular education programs with an emphasis on proficiency and specialization. Also, in 2010 the government initiated a combined approach to enable such alignment through the action plan for strengthening the linkages between employment and Technical Vocational Education and Training (TVET).